Yearlong analysis of bacterial diversity in hospital sink drains: culturomics, antibiotic resistance and implications for infection control - Laço, José; Martorell, Sergi; Gallegos, Maria del Carmen; Gomila, Margarita (Frontiers in Microbiology, 2025)
Hospitals can carry high levels of bacterial diversity from all types of origins, such as human skin, outside environment and medical equipment. Sink drains in clinical settings are considered reservoirs for pathogenic bacteria and potential sources of hospital-acquired infections (HAI’s) and antibiotic resistance genes (ARGs). Therefore, infection control measures are crucial to minimizing the risks associated with these reservoirs. Recent research has focused primarily on intensive care units (ICUs) and known pathogens, often employing metagenomic approaches that do not include bacterial isolation. This study aims to evaluate bacterial diversity using culturomics, extending the investigation beyond the ICU to identify antibiotic-resistant bacteria. A total of four samplings were conducted over 1 year (March 2022 to March 2023) in five different hospital wards [ICU, General Medicine (GM), Hematology (H), Short stay unit (UCE), and Microbiology laboratory (MS)]. All samples were cultured on selective and non-selective culture media, resulting in 1,058 isolates identified using MALDI-TOF MS, with a subset confirmed through 16S rRNA gene sequencing. Isolates retrieved from antibiotic supplemented agar were subjected to antibiotic susceptibility testing. The highest bacterial diversity, as measured by the Shannon index, was observed in the ICU and GM wards, posing significant risks to patients in these areas. While bacterial genera were largely similar across wards and sampling times, with Pseudomonas and Stenotrophomonas being the most prevalent, different species were detected in each sampling, indicating no loss of diversity. This suggests that these environments undergo dynamic changes over time, influenced by their surroundings. The results also indicate a relationship between human activity and drain usage and the presence of Pseudomonas aeruginosa, the most commonly found species across most wards. Antibiotic susceptibility testing revealed that all tested isolates, except for one, were multi-resistant, including clinically relevant species, such as P. aeruginosa and K. pneumoniae. Hospital drains may serve as reservoirs for both known and emerging pathogens exhibiting high antibiotic resistance phenotypes. Their dynamic nature may provide insights into strategies for preventing the colonization of these environments by such species.